Edge-gold-coated silver nanoprisms : enhanced stability and applications in organic photovoltaics and chemical sensing - Shahjamali, Mohammad M. (2014)
We report a facile synthetic route for edge-gold-coated silver nanoprisms (GSNPs) and their comprehensive optical and structural characterization. The GSNPs exhibit remarkably high stability toward chemical etching and excellent performance as both optical antennae for light-harvesting applications and refractive index sensors. We show that when embedded into a photovoltaic bulk heterojunction film of poly(3-hexylthiophene)/phenyl-C61-butyric acid methyl ester (P3HT/PCBM), plasmonic GSNPs act as optical antennae to substantially enhance light absorption in the active organic solar cell layer. We measure a ≈7-fold enhancement in the polaron generation yield through photoinduced absorption spectroscopy. Owing to the high stability, large sensitivity factors, and strong field enhancement effect, these GSNPs exhibit great potential as optical probes for sensing and photovoltaic applications. We also show that the refractive index sensing figure of merit (FoM) of GSNPs can reach 4.05 RIU–1 and suggest based on finite-difference time-domain (FDTD) calculations that the FoM of GSNPs could reach even higher values with better control of particle dispersity.